Roles of microRNA-15 family in normal and pathological late lung development - Sakkas, Elpidoforos; Justus Liebig University Giessen (My University, 2016)
MicroRNAs are key regulators of organogenesis and during the last years many studies focused on microRNA expression during embryonic development. To date, there is no study to report possible roles of microRNAs in late lung development and especially during the alveolarization process.The objective of this study was to identify microRNAs that are deregulated under hyperoxic conditions and to assess whether microRNA expression can be modulated in vivo. Lung microRNA expression screening was assessed at four time points under normoxic conditions by microRNA microarray; the time points were P2.5 and P3.5 (pre-septation), P5.5 (peak septation) and P14.5 (post-septation). Also, lung microRNA expression screening was assessed in pups exposed to hyperoxia (85% O2) for 14 days. In total, 55 microRNAs were deregulated. Amongst the most up-regulated microRNAs were miR-15b and miR-497, both belong to miR-15 family. Target prediction analysis suggested that miR-15 family regulates Smad7 expression. Using a luciferase-based reporter assay, Smad7 was validated as a direct target of miR-15b suggesting an impact on TGF-beta signaling during alveolarization. In vitro, overexpression of miR-15b and miR-497 down-regulated Smad7 expression and increased TGF-beta responsiveness, as assessed by a p(CAGA)9 reporter assay in primary lung fibroblasts.In vivo silencing of miR-15b and miR-497 (by using LNA-antagomirs) restored alveolarization by ~50 % in developing lungs of mouse pups exposed to hyperoxia and was assessed by using a stereological approach. The mean linear intercept (MLI) was notably decreased in the hyperoxia treated group but the septal thickness (St) remained unchanged. These data reveal a causal role for the deregulated miR-15 family in arrested lung development associated with hyperoxia exposure. These data are also the first to report that microRNA inhibition, using LNA-antagomirs, is a viable interventional method to restore perturbed alveolarization.

MicroRNAs sind die Schlüsselregulatoren der Organentwicklung. Deshalb wurde in den letzten Jahren viel auf dem Gebiet der microRNA Expression während der Embryonalentwicklung geforscht. Heutzutage gibt es noch keine Studien, welche die Rolle der microRNAs in der späten Lungenentwicklung, und besonders während der Alveolarisierung, postulieren.Das microRNA-Screening der Lunge via microRNA microarray unter normoxischen Bedingungen ist an 4 Zeitpunkten durchgeführt worden, diese sind: P2.5 und P3.5, P5.5 und P14.5. Ebenso wurde mit Neonaten (Maus) verfahren, die für 14 Tage hyperoxischen Bedingungen ausgesetzt waren.Insgesamt sind 55 microRNAs dereguliert. Die am meisten hochregulierten microRNAs sind miR-15b und miR-497, beide gehören zur miR-15-Familie. Anhand der target prediction Analyse wurde angedeutet, dass die miR-15-Familie die Smad7-Expression reguliert. Mit dem luciferase-based reporter assay wurde bestätigt, dass miR-15b ein direktes Ziel von Smad7 ist und dies Auswirkungen auf die TGF-beta Signalwirkung während der Alveolarisierung haben könnte.In vitro hatte die Überexpression von miR-15b und miR-497 eine schwächere Smad7-Expression und erhöhte TGF-beta Empfindlichkeit zur Folge, wie dies ebenso mit dem p(CAGA)9 reporter assay in primären Lungenfibroblasten bestätigt wurde. In vivo Silencing von miR-15b und miR-497 (mit LNA-antagomirs) führt zu einer Wiederherstellung der Alveolarisierung von ~50 % in Neonaten (Maus), die hyperoxischen Bedingungen ausgesetzt waren. Die Auswertung erfolgte hierbei mit einem Stereologieverfahren. Der mean linear intersept (MLI) ist in der hyperoxischen Gruppe erheblich reduziert wobei die Septumdicke unverändert bleibt.Diese Ergebnisse zeigen einen kausalen Zusammenhang zwischen deregulierten microRNAs der miR-15-Familie und gehemmter Lungenentwicklung unter hyperoxischen Bedingungen. Weiterhin zeigen diese Ergebnisse, dass Inhibierung der microRNA mit LNAantagomirs eine praktikable Therapie für gestörte Alveolarisierungsprozesse sein kann.
Keywords: microRNA; lung development; ddc:610